ProMMP-1 PRODUCTION BY CULTIVATED CELLS OF VASCULAR ENDОTHELIUM IN VITRO AND IN A HUMAN BODY - N. N. Scliankina (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. Matrix metalloproteinases (MMP) are structurally related endopeptidase composed of active sites which include ions Zn2+ and Ca2+. Cultured cells of human blood vessels produce MMP-1, proteolytic effect is aimed at splitting the collagen I and III types, and subsequent vascular remodeling. MMP-1 is synthesized as an inactive zymogen proMMP-1. It was shown that interferon alpha, beta and gamma inhibited production by culture of HUVEC proenzyme MMP-1, which seems to characterize their anti-angiogenic action. The effect of immunomodulators is more difficult to explain: perhaps inhibiting effect of imunofan and, as well as activating effect of cycloferon due to their internal structural peculiarities. The action of interferon alpha, beta and gamma, used as HUVEC before infection with HSV-1, and after it led to decrease in production proMMP-1. Apparently, the antiangiogenic effect of IFN is saved in the case of infection of cultures of vascular endothelium with HSV-1. Scatter in the content of proMMP-1 in the serum of blood donors was 1.625–11.8 ng/ml and in patients with chronic microbial-viral infections was 1.22–21.16 ng/ml. Higher rates of proMMP-1 were in older patients group. To estimate the system of MMP in vitro, and in the body a comprehensive study must be conducted, including proMMP-1, the active form of proenzyme and specific inhibitor of MMP-1.